Meningkatkan Keaktifan dan Hasil Belajar Siswa Kelas V pada Materi Daur Air dengan Model PBL - Siti Mulyani; Maria Agustina Amelia; Merciana Sarwi (Universitas Indraprasta PGRI Jakarta, 2023)
The activeness of students in participating in learning in class V of Kanisius Kintelan I Elementary School in science lessons was not yet seen and at the end of learning the learning outcomes of many students still received low scores. This study aims to test the Problem Based Learning (PBL) learning model to increase student activity and learning outcomes in science lessons on the water cycle material. The water cycle material that is the focus of the research is material studied by students in class V in the even semester. This research is Classroom Action Research type, which was conducted in class V for the 2022/2023 school year at Kanisius Kintelan I Elementary School, Mergangsan District, Yogyakarta. Data collection was carried out through observation during the learning process and the results of the pre-test and post-test. The data analysis technique used is descriptive quantitative and descriptive qualitative analysis techniques. The results of observations on the learning process were discussed as qualitative data, while student test results are discussed as quantitative data. This study showed an increase in the activity and learning outcomes of fifth grade students at Kanisius Kintelan I Elementary School in the water cycle material.